Linear algebra - Schäffer, Juan Jorge (World Scientific, 2014)
In the spirit of the author's Basic Language of Mathematics, this companion volume is a careful exposition of the concepts and processes of Linear Algebra. It stresses cautious and clear explanations, avoiding reliance on co-ordinates as much as possible, and with special, but not exclusive, attention to the finite-dimensional situation. It is intended to also serve as a conceptual and technical background for use in geometry and analysis as well as other applications. Contents: Linear Spaces and Linear Mappings; Properties of Linear Mappings; Linear Products and Coproducts; Families in Linea.